Establishment of crops under minimal soil disturbance and crop residue retention in rice-based cropping system: Yield advantage, soil health improvement, and economic benefit - Salahin, Nazmus; Jahiruddin, Mohammad; Islam, Mohammad Rafiqul; Alam, Md. Khairul; Haque, M. Enamul; Ahmed, Sharif; Baazeem, Alaa; Hadifa, Adel; EL Sabagh, Ayman; Bell, Richard W. (MDPI, 2021)
Minimum soil disturbance and increased crop residue retention practices are promising options to enhance soil organic matter, nutrient concentration and crop yield. However, the potentials of the practices in improving soil properties, increasing crop yield and in ensuring economic return have not been tested in the monsoon rice (Oryza sativa L.)-lentil (Lens culinaris L.)/wheat (Triticum aestivum L.)-jute (Corchorus culinaris L.) cropping systems on seasonally flooded lowlands of the Eastern Gangetic Plain of South Asia. A field trial for consecutive three years was conducted in the Gangetic Plains of Bangladesh to evaluate the effects of zero tillage (ZT), strip-tillage (ST), bed planting (BP) and conventional tillage (CT) with two residue retention levels (RL—a low level similar to current farmers’ practice and RH—increased retention) on soil properties, yield and economic return. Between rice and jute crops, lentil was grown for the 1st and 2nd years and wheat for the 3rd year during the dry winter season. The ST and BP performed better than the CT and ZT in terms of yield of rice and lentil, whereas ST and ZT performed better than other practices in the case of jute. Higher residue retention (RH) increased crop yield for all the years. The highest rice equivalent yield (sum of 3 crop yields, expressed as rice yield) and the greatest benefit-cost ratio (BCR) were recorded with ST and RH. The increased yield in the ST was associated with reduced soil bulk density (BD), while ST with RH increased soil water (SW) and decreased penetration resistance (PR) of soil. Compared to CT, minimum soil disturbance of ZT and ST increased soil organic matter (SOM) stock by 24% and 23%, respectively; total nitrogen (TN) by 23.5% and 18.4%, respectively; extractable sulphur (S) by 21% and 18%, respectively; whereas Zinc (Zn) concentrations increased by 53% and 47%, respectively, in the upper 0–5 cm soil depth. Accumulation of extractable P, S and Zn in the 0–5 cm depth of soil followed the sequence as ZT > ST > BP > CT practice. The higher amount of residue retention significantly increased SOM, TN and extractable P, K, S and Zn concentrations at 0–5 cm and 5–10 cm soil depths. The 3-year study suggests that ST with RH is a potential crop management approach for the seasonally flooded rice-lentil/wheat-jute cropping systems to enhance soil nutrients status, crop yield and farm economy.